PLZKLME - Emmerling, Leonhard; Engels-Schwarzpaul, A.-Chr.; Chichon, F (Interstices: Journal of Architecture and Related Arts, 2007)
Leonhard Emmerling Translation by A.-Chr. Engels-Schwarzpaul and F. Chichon